Common coupled fixed point theorems for two hybrid pairs of mappings satisfying an implicit relation - Deshpande, Bhavana; Handa, Amrish (Sarajevo Journal of Mathematics, 2015)
We establish two common coupled fixed point theorems for two hybrid pairs of mappings satisfying an implicit relation under weak commutativity and $w-$compatibility on a complete metric space, which is not partially ordered. We do not use the condition of continuity of any mapping for finding the coupled coincidence and common coupled fixed point. We improve, extend and generalize several known results.